Study of reactivity pattern of hormone receptors in patients with breast cancer at a tertiary care hospital, Aurangabad, India - George, Greeshma Ann; Mulay, S. S.; Borde, Neha; Antony, Philips (International Journal of Research in Medical Sciences, 2019)
Background: Breast cancer is one of the most common malignancies affecting the female population worldwide. Prognosis and management of breast cancer are influenced by variables such as stage, grade, and hormone receptor status. Tumours that express ER and/or PR have a better prognosis and most of them respond well to hormonal therapy. In addition to hormone receptors, HER2 has emerged in recent years as an important independent predictive marker. Methods: All surgically operated female cases of breast carcinoma which were submitted for immunohistochemistry test for estrogen, progesterone and human epidermal growth factor receptor-2 in the Department of Pathology, MGM Medical College, Aurangabad for the duration of December 2015 to October 2017 were included in this prospective study. A total of 50 patients were taken up for the study. Results: The maximum age of the patients were in the 4th -5th decade and were mostly premenopausal. The tumour was maximum involving the right breast, upper outer quadrant and were BI-RADS 4. Majority were grade 2 and were invasive ductal carcinoma. Hormone receptor status showed ER positivity 48%, PR positivity 46% and HER2 positivity 28%. Conclusions: So, to conclude, immunohistochemical analysis of ER, PR and HER2 receptors is widely available at a reasonable cost and provides valuable prognostic, predictive and therapeutic information. Although we could see different patterns of hormonal receptor status, irrespective of the histological grade, type and lymph node status in our study, HER2 testing along with ER/PR status should be performed routinely in all the patients diagnosed of breast cancer as this will help the clinicians to manage the patients further.